2006
DOI: 10.3892/or.15.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HER2 gene amplification assessed by fluorescence in situ hybridization and HER2 protein expression assessed by immunohistochemistry in gastric cancer

Abstract: A monoclonal antibody to HER2 protein is widely used in the treatment of patients with HER2-overexpressing breast cancer and has also been found to exhibit antitumor activity in human gastric cancer cells that overexpress HER2. The purpose of this study was to evaluate the frequency of HER2 overexpression and concordance between the results for protein expression and gene amplification in both surgical and biopsy specimens of gastric cancer as assessed with two commercial kits, one for immunohistochemistry (IH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
131
2
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(158 citation statements)
references
References 22 publications
18
131
2
7
Order By: Relevance
“…between duplicate TMAs constructed from the same tissue section in a patient were 74.5 and 91.8 %, respectively. Although this was in good agreement with the previously reported results of analysis of biopsy specimens from 261 patients with invasive intestinal-type gastric cancers [25], further investigations are still required to elucidate the reliability of HER2 scoring in TMA samples in gastric cancer.…”
Section: Discussionsupporting
confidence: 81%
“…between duplicate TMAs constructed from the same tissue section in a patient were 74.5 and 91.8 %, respectively. Although this was in good agreement with the previously reported results of analysis of biopsy specimens from 261 patients with invasive intestinal-type gastric cancers [25], further investigations are still required to elucidate the reliability of HER2 scoring in TMA samples in gastric cancer.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported to be overexpressed in 20% of breast and 22% of gastric cancers, although different studies have reported varying results (Bang et al, 2010;Arteaga et al, 2011). In a study investigating 200 patients, HER2 overexpression was reported in 23% of patients, while another study that analyzed 248 patients showed overexpression of HER2 mRNA and/or proteins and amplification of genes in 22.6% of patients (Yano et al, 2006;. In routine clinical practice, HER2 status is usually assessed by IHC or FISH/CISH/SISH techniques in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These findings clearly show that CD90 potentially has a value as a target for immunotherapy. ERBB2 amplification is found in 20-30% of gastric carcinomas and is reported to be significantly associated with shorter survival of cancer patients (Tanner et al, 2005;Yano et al, 2006;Marx et al, 2009). How ERBB2 signaling affects tumor growth, invasion and metastasis is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The ERBB2 (HER2) gene is amplified in approximately 20-30% of human breast and gastric cancers, in which it is associated with aggressive disease and early development of metastasis (Slamon et al, 1989;Tanner et al, 2005;Yano et al, 2006). A significant correlation between ERBB2 overexpression and expression of the stem cell marker ALDH1 has been found in a series of 491 breast cancer patients (Ginestier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%